2021
DOI: 10.5851/kosfa.2021.e17
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics/Probiotics Mixture Induced Changes in Cecal Microbiome and Intestinal Morphology Alleviated the Loperamide-Induced Constipation in Rat

Abstract: The aim of this study was to investigate the effect of a mixture of multi-strain probiotics and prebiotics on loperamide-induced constipation in Sprague-Dawley rats. A multi-strain probiotic alone (loperamide-induced group with multi-strain probiotic mixture group; Lop-Pro) and a mixture of multistrain probiotics and prebiotics (loperamide-induced group with multi-strain probiotic and prebiotic mixture group; Lop-Pro/Pre) were administered orally after inducing constipation. The fecal water content was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…55,56 Increasing attention has been paid to the application of probiotics therapy in constipation treatment. 57–60 Probiotics can improve gut dysmotility and alleviate symptoms by modulating the gut microbiota, microbial metabolites, central and enteric nervous systems, as well as the immune system. 61…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 Increasing attention has been paid to the application of probiotics therapy in constipation treatment. 57–60 Probiotics can improve gut dysmotility and alleviate symptoms by modulating the gut microbiota, microbial metabolites, central and enteric nervous systems, as well as the immune system. 61…”
Section: Discussionmentioning
confidence: 99%
“…55,56 Increasing attention has been paid to the application of probiotics therapy in constipation treatment. [57][58][59][60] Probiotics can improve gut dysmotility and alleviate symptoms by modulating the gut microbiota, microbial metabolites, central and enteric nervous systems, as well as the immune system. 61 Based on the analysis of gut microbiota composition, we found that LGGs promoted the growth of Allobaculum, which was reported as a beneficial bacterial species.…”
Section: Papermentioning
confidence: 99%
“…Yoghurt containing Lactococcus lactis , Lactobacillus plantarum , and Lactobacillus casei promoted higher relative abundance of Bacteroidetes phylum and lower abundance of Firmicutes phylum in mice intestine (Liu et al, 2017). Kim et al (2021) found that intake of multistrain probiotics increased the abundance of Bacteroidetes in the intestinal microbiota of Sprague–Dawley rats induced by loperamide. In addition, decreasing the ratio of F/B in the intestine, regulating intestinal pH, and improving the environment for beneficial bacteria to flourish can correct intestinal microecological disorders in constipated patients (Li et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 60 mice were used. Constipation was induced as described by C. L. Chen et al (2020) and Kim et al (2021) with minor modifications. After 7 days of adaptation, 48 mice among them were administered with 5 mg/kg BW loperamide hydrochloride by gavage daily to induce constipation for 1 week, and the rest 12 mice were orally administrated with equal volume of normal saline and used as normal group.…”
Section: Methodsmentioning
confidence: 99%
“…e protocol of these experiments was approved by the Animal Ethics Committee of Hunan University of Chinese Medicine (approval number LL2021091502). Loperamide hydrochloride capsules were used to induce constipation, as previously described [18,19]. ese loperamide hydrochloride capsules were manufactured by Xian Janssen Pharmaceutical Ltd. and were purchased from the Pharmacy of the First Affiliated Hospital of Hunan University of Chinese Medicine, Changsha, China, with OTC No.…”
Section: Animalsmentioning
confidence: 99%